Numerical Study of Solutions of the 3D Generalized Kadomtsev-Petviashvili Equations for Long Times (Communications in Computational Physics, 2020)
From a spectral method combined with a predictor-corrector scheme, wenumerically study the behavior in time of solutions of the three-dimensional generalizedKadomtsev-Petviashvili equations. In a systematic way, the dispersion, the blowupin finite time, the solitonic behavior and the transverse instabilities are numericallyinspected.